Free Radical Scavenger Specifically Prevents Ischemic Focal Ventricular Tachycardia - Xing, Dezhi (2009)
BACKGROUND: Focal ventricular tachycardia (VT) in acute myocardial ischemia is closely related to triggered activity (TA), which may be blocked by scavenging reactive oxygen species (ROS). OBJECTIVE: This study analyzed effects of acutely administered ROS scavenger-2,2,6,6-tetramethylpiperidine-N-oxyl (TEMPO) on VT in vivo and TA in vitro. METHODS: Forty-three alpha chloralose anesthetized dogs with coronary artery occlusion were studied. 3-D activation mapping helped to locate the origin of focal or reentrant VT. TEMPO (30mg/kg, iv) or vehicle was given. Endocardium excised from the site of origin of VT was studied using standard microelectrode techniques and measures of ROS. RESULTS: Reentry and focal VT induction were both highly reproducible. TEMPO blocked focal VT in 6 of 11 dogs (p<0.05), but 9 of 9 dogs with reentrant VT continued to have VT re-induced after TEMPO. TEMPO did not alter effective refractory period (168±3 to 171±3 ms), mean blood pressure (88±3 to 81±3 mmHg), and size of ischemia (42±3% vs 40±4%). In vitro, TEMPO (10(−3)M, n=14) produced no change in action potentials. Nevertheless, TA was reversibly attenuated from 5.3±1.1 to 0.4±0.4 complexes with TEMPO (n=15, p<0.05). Lucigenin-enhanced chemilumenescence and dihydroethidium staining showed increased ROS in ischemic endocardium; TEMPO dramatically reduced ROS in ischemic sites. CONCLUSIONS: TEMPO, a scavenger of ROS, prevented triggered activity associated with focal VT during myocardial ischemia in areas of increased ROS. Antioxidant therapy may play an important role in blockade of focal VT under the conditions of myocardial ischemia.